A new hope? FIFA 2.0, FIFA Women`s Football Strategy, and event bidding for the 2023 FIFA Women`s World CupTM - Beissel, A. S.; Postlethwaite, V.; Grainger, A.; Brice, J. (Soccer & Society, 2024)
The FIFA Women`s World CupTM 2023 (FWWC23) bidding process was the first major women`s football tournament awarded following FIFA`s landmark reform package known as FIFA 2.0: The Vision for the Future. This paper interrogates the conjunctural politics of the FWWC23 competitive bid process, exploring the unique ways in which FIFA shapes, influences, and controls event bidding for the FIFA Women`s World Cup. Based on an analysis of official documents, bid books, and news media coverage connected to the FWWC23 bid process, this paper presents how varying FIFA-based narratives and tactics shaped the winning Australia and New Zealand bid. Based on our analysis, four key points of discussion emerged in relation to the ways in which FIFA 2.0 shaped, and was shaped by, FWWC23 event bidding: the formation of bid "products"; the governance of the bid "process"; the politics of bid "positioning"; and the advancement of FIFA "priorities".